Analisis Arus Kas Operasi Dan Laba Terhadap Return Saham pada Perusahaan Manufaktur Cigarette - Ulfa, Dewi Maria; Pratiwi, Yanna Eka; Lastianti, Siwidyah Desi (JFAS : Journal of Finance and Accounting Studies, 2024)
The purpose of this study is to analyze the effect of operating cash flow and profit on the investment results of cigarette manufacturing companies' shares on the Indonesia Stock Exchange 2019–2022. Secondary data were collected as part of quantitative research methodology. Cigarette manufacturing companies listed on the Indonesia Stock Exchange at the time constituted the study population. Purposive sampling is used to select research samples. The Structural Equation Model (SEM) - Partial Least Square (PLS) analysis approach was used in this study, and SmartPLS 3.0 software was used to handle the data. The findings show that operating cash flow has no noticeable impact on stock performance. This result shows that the value of stock investment returns is not significantly affected by the increase in revenue in cigarette manufacturing companies.Cash Flow